PEMBANGUNAN KAWASAN PEMUKIMAN DENGAN KONSEP KEBENCANAAN DI KABUPATEN BOGOR - Aam Amirudin; Syamsul Maarif; I Dewa Ketut Kerta Widana (Republic of Indonesia Defense University, 2021)
Bogor Regency as an area that is a buffer for the capital city of Jakarta is an alternative choice that is very popular considering some of the ease of available facilities ranging from transportation facilities, beauty, and natural beauty including the availability of large enough land for settlement. In addition to saving a million charms to become a residential area, Bogor Regency is also one of the areas prone to landslides and floods. In order to meet the need for settlements, it is necessary to apply the concept of disaster by considering all risks that may occur technically and regulations by taking a preventive approach consistently during the planning of the settlement development. The method used by the author in this study is a qualitative method with a literature study design and a phenomenological approach. The results show that some settlements have not fully implemented the concept of disaster as a conscious and anticipatory effort in minimizing disaster risk so that safe and comfortable conditions arise for their residents, in addition to achieving community welfare in order to improve national security.